CO2 dissolution and its impact on reservoir pressure behavior. (December 2015) - Peters, E.; Egberts, P.J.P.; Loeve, D.; Hofstee, C.
Highlights: Estimation of the effect of CO2 dissolution on pressure for CO2 stored in aquifers. Estimates of CO2 dissolution taking into account convective mixing. Efficient model for pressure estimation based on volume balance approach. Pressure decrease found to be relevant for monitoring only for thin layers of CO2 . Range of relevant storage reservoir included in the analysis. Abstract: Geological storage of CO2 in large, saline aquifers needs to be monitored for safety purposes. In particular the observation of the pressure behavior of a storage site is relevant for the indication of CO2 leakage. However, interpretation of observed pressure is not straightforward in these systems, due to the large number of natural processes that affects the pressure. These processes include pressure dissipation across aquifer boundaries for which both location and transmissibility are uncertain, pressure dissipation in low-permeable deposits surrounding the aquifer, dissolution of CO2 into the brine and chemical reactions. In this paper we will focus on the aquifer pressure effects of dissolution of CO2 in brine which can be significantly enhanced by density-driven convective mixing. The convective mixing occurs because the density of brine increases due to the dissolution of CO2, creating an unstable layer of dense brine below the CO2 plume. This layer may induce vertical, density-driven convective flow in so-called fingers. We have studied the effect of convectively-enhanced CO2 dissolution on the pressure in a CO2 storage site for 50 years using a volume balance model. This showed that only for reservoirs with very high permeability (>500 mD in vertical direction) and a thin CO2 layer (<2–3 m), the pressure reduction due to CO2 dissolution enhanced by convective mixing is important (>0.05 bar/yr). For most examples simulated here, the effect of CO2 dissolution on the pressure was minor (<0.02 bar/yr or <0.2% of the pressure increase due to CO2 injection per year).